Diagnosis Hama Penyakit Tanaman Bawang Merah Menggunakan Metode Neighbors Weighted K-Nearest Neighbors (NWKNN) - Masayu Vidya Rosyidah; Budi Darma Setiawan; Muhammad Tanzil Furqon (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Red onions is a a plant that is a successfull export commodity in Indonesia. Red onions have many benefits, can be a seasoning cook to medical ingredients. Behind that, during the planting period these plants often run the risk of crop failure caused by pests and diseases of red onions. In addition, there is still a lack of understanding of farmers in controlling pests and diseases causing inevitable losses. One way to overcome this problem is to build a system that can diagnose pests and diseases on red onions, namely the expert system. The expert system that is built to diagnose pests and diseases on red onions in this study using the Neighbors Weighted K-Nearest Neighbors (NWKNN) method with parameters k =2 and e = 4 produces an accuracy of 100%.